European Union and Central Asia – past directions and future perspectives - Ana-Maria Anghelescu (CES Working Papers, 2018)
In 2007, the European Union launched a targeted Strategy for Central Asia, as a continuation of the efforts to improve the relations with the five post-soviet republics. The adoption in 2019 of a new EU Strategy for Central Asia offers the opportunity to include in the new strategic framework the lessons learned during the past decade of promoting the EU influence in the region, besides promoting measures to strengthen EU's global posture. The aim of this paper is to evaluate the capacity of the EU to mobilise resources for its foreign policy goals, specifically in relation with Central Asia. In examining this idea, I will use the framework offered by the neoclassical realist theory, mainly because in relation to some foreign policy objectives, the EU can be assimilated to a state.
Keywords: 330; Strategy of the European Union for Central Asia; neoclassical realism; foreign policy implementation; resource extractive state